Preparation method and application of composite metal organic framework sulfur catalyst with core-shell structure
By using core-shell structure composite metal organic frame sulfur catalyst in sodium-sulfur batteries, the problems of low sulfur utilization and poor circulation performance in traditional sodium-sulfur batteries are solved, and higher conversion efficiency and circulation stability of active substances are achieved, improving the improvement of The overall performance of the battery.
Patent Information
- Application Number
- CN202311162263.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2024-12-20
AI Technical Summary
When using liquid electrolyte, traditional lithium-sulfur batteries and sodium-sulfur batteries cause shuttle effects due to sulfur insulation and polysulfide dissolution, resulting in low sulfur utilization and poor circulation performance, affecting electrochemical performance.
The metal organic frame ZIF67 material is prepared by solvent method using core-shell structure composite metal organic frame sulfur catalyst, and the high-entropy metal organic frame cladding layer is grown on its surface by epitaxial growth method to form a core-shell structure composite material for sodium sulfur As sulfur catalyst in the battery.
It significantly improves the conversion kinetics and utilization of active substances in sodium-sulfur batteries, reduces the shuttle effect, maintains the cycling stability of polysulfides in the electrolyte, and improves the overall electrochemical performance of sodium-sulfur batteries.
Smart Images

Figure CN119158624A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material chemistry, and specifically relates to a preparation method of a core-shell structure composite metal organic framework sulfur catalyst and application thereof. Background Art
[0002] The main energy sources in the world today are about 37% oil, 25% natural gas, 21% coal, 9% nuclear energy and 3% renewable energy. Renewable energy includes geothermal energy, solar energy, wind energy, biomass energy, hydropower, etc. As people's demand for energy continues to increase, the environmental problems caused by energy mining are becoming increasingly serious. Therefore, the development of renewable energy production, transportation, conversion and storage is a global problem that urgently needs to be solved. Improving new energy storage technology is mainly used to store renewable energy, such as wind energy, tidal energy, etc., to support the driving of electric vehicles and electric vehicles, and to support the use of portable electronic products, such as our daily mobile phones, cameras, laptops, etc.
[0003] As we all know, lithium-ion batteries are the most widely used. However, the theoretical energy density of traditional lithium-ion batteries is about 387Wh kg -1 This limits its wide application in power vehicles and pure electric vehicles. The theoretical energy density of lithium-sulfur batteries is as high as 2500Wh kg -1 , the theoretical specific capacity is up to 1675mAh g -1 , and has attracted widespread attention, and sulfur has the advantages of low cost, non-toxicity, and good safety. However, due to the scarcity of lithium in the earth's crust, it only accounts for about 0.0065% and is expensive, while sodium accounts for about 2.64%. The electrode potential of sodium is -2.71V, slightly higher than that of lithium -3.02V, and is safer. Moreover, sodium and lithium are in the same main group and have similar electrochemical properties, so sodium can be used to replace lithium to construct sodium-sulfur batteries.
[0004] However, since metallic sodium is more active than lithium, sodium-sulfur batteries face more challenges than lithium-sulfur batteries, especially in terms of the utilization of sulfur active materials and capacity retention during cycling. Similar to lithium-sulfur batteries, room temperature sodium-sulfur batteries have low sulfur utilization and poor cycling performance when using liquid electrolytes due to the insulation of sulfur, the easy dissolution of polysulfides in the electrolyte, and the shuttle effect, volume expansion, etc., which seriously affect the electrochemical performance of sodium-sulfur batteries. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a core-shell structured composite metal organic framework sulfur catalyst and its application. The prepared catalyst has high catalytic efficiency and stronger catalytic performance. When applied to sodium-sulfur batteries, it can significantly improve the conversion kinetics and actual utilization rate of active substances in sodium-sulfur batteries, reduce the shuttle effect, and maintain the cyclic stability of polysulfides in the electrolyte.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a core-shell structure composite metal organic framework sulfur catalyst, which uses a solvent method to prepare a metal organic framework ZIF67 material, and then uses an epitaxial growth method to grow a layer of high entropy metal organic framework coating layer on the surface of the metal organic framework ZIF67 material. The formed core-shell structure composite metal organic framework material is a sulfur catalyst.
[0007] The method for preparing the core-shell structure composite metal organic framework sulfur catalyst specifically comprises the following steps:
[0008] Step 1: Prepare the metal organic framework ZIF67 material using the solvent method:
[0009] Dissolve 3-5 g of 2-methylimidazole in 10-20 ml of deionized water and continue stirring until uniform to obtain solution A;
[0010] Dissolve 0.1-0.5 g of cobalt acetate and 0.05-0.2 g of hexadecyltrimethylammonium bromide in 30-60 ml of deionized water, and continue stirring until uniform to obtain solution B;
[0011] Solution B is added to solution A, followed by continuous stirring for 3 to 6 hours at a speed of 600 to 1200 rpm;
[0012] The mixed solution was transferred to a reaction vessel and reacted at 95-115°C for 12-24 hours;
[0013] After the reaction is completed, the product is collected by centrifugation to obtain the metal organic framework ZIF67 material;
[0014] Step 2: Prepare core-shell structure composite metal organic framework materials using epitaxial growth method:
[0015] Disperse 1-2 g of the metal organic framework ZIF67 material prepared in the first step and 3-5 g of 2-methylimidazole in 150-200 ml of methanol, and continue stirring until uniform to obtain solution C;
[0016] Dissolve 0.1-0.5 g of ferric nitrate, 0.1-0.5 g of cobalt nitrate, 0.1-0.5 g of nickel nitrate, 0.1-0.5 g of copper nitrate and 0.1-0.5 g of molybdenum nitrate in 30-60 ml of methanol, and continue stirring until uniform to obtain a solution D;
[0017] Slowly add solution D to solution C, and then continue stirring for 6 to 12 hours at a speed of 500 to 800 rpm;
[0018] After the reaction is completed, the product is collected by centrifugation to obtain a core-shell structured composite metal-organic framework material.
[0019] The above core-shell structure composite metal organic framework sulfur catalyst is used as a sulfur catalyst for sodium-sulfur batteries.
[0020] Preferably, sulfur is doped into the core-shell structure composite metal organic framework material by ball milling and hot melting method to obtain a sulfur-composite metal organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
[0021] Furthermore, the specific application process is: putting the core-shell structure composite metal organic framework sulfur catalyst and pure phase nano sulfur powder into a ball mill according to a mass ratio of 1: (2 to 5), using a planetary ball mill to mix and treat for 3 to 5 hours at a rotation speed of 500 to 800 rpm, putting the mixture after ball milling into a tubular furnace under nitrogen protection, and heat treating it at 100 to 200° C. for 8 to 24 hours to obtain a sulfur-composite metal organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The core-shell structure composite metal organic framework material prepared by the present invention has a metal organic framework ZIF67 material as the core, and the outer layer of the metal organic framework ZIF67 material is coated with a high entropy metal organic framework shell. The core-shell structure composite metal organic framework material has the following advantages when used as a sulfur catalyst for a sodium-sulfur battery:
[0024] 1) Overall structural advantages. On the one hand, the core-shell structure composite metal-organic framework material can inherit the advantages of high specific surface area and high porosity of the metal-organic framework, providing sufficient space for subsequent sulfur loading; on the other hand, the porous structure of the core-shell structure composite metal-organic framework material can fix polysulfides by confinement effect and physical adsorption, inhibit the diffusion of polysulfides, and thus achieve the effect of slowing down the shuttle effect.
[0025] 2) Advantages of the core-shell structure. The simple metal organic framework ZIF67 has been used in sulfur catalysts. Although it can improve the catalytic performance to a certain extent, it still cannot effectively improve the actual long-cycle stability. The core-shell structure composite metal organic framework material prepared by the present invention takes ZIF67 as the core, which not only retains the advantages of ZIF67 itself, but also covers a layer of high entropy metal organic framework shell on the surface of ZIF67. The design of the core-shell structure forms a large number of interfaces between ZIF67 and high entropy metal organic frameworks. A large number of electron transfers will occur at the interface, thereby affecting the electronic structure and coordination environment of the metal atoms, breaking the original complete stable electronic structure, making the metal atoms at the interface more inclined to interact with external atoms, thereby producing a more effective anchoring and catalytic effect on the polysulfides generated during the charging and discharging process of the sodium-sulfur battery, and achieving the purpose of improving the overall sodium-sulfur battery cycle stability.
[0026] 3) Advantages of high entropy metal organic framework. The present invention coats the surface of ZIF67 with a high entropy metal organic framework. Due to the presence of multiple metal atoms in the high entropy metal organic framework, it exhibits an uneven electron distribution, that is, a stronger catalytic activity. At the same time, due to the competition between multiple metal atoms, it will further affect the electronic structure of the organic ligand, so that the anions and cations work together to improve the catalytic performance of the overall material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the core-shell structure composite metal organic framework sulfur catalyst prepared in Example 1;
[0028] Figure 2 This is the discharge specific capacity cycle diagram of the sulfur-composite metal organic framework material prepared in Example 1. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below with reference to the accompanying drawings.
[0030] Example 1: A method for preparing a core-shell structured composite metal organic framework sulfur catalyst, comprising the following steps:
[0031] Step 1: Prepare the metal organic framework ZIF67 material using the solvent method:
[0032] Dissolve 4 g of 2-methylimidazole in 15 ml of deionized water and continue stirring until homogeneous to obtain solution A;
[0033] Dissolve 0.2 g of cobalt acetate and 0.1 g of hexadecyltrimethylammonium bromide in 50 ml of deionized water and continue stirring until uniform to obtain solution B;
[0034] Solution B was added to solution A, followed by continuous stirring for 4 hours at 800 rpm;
[0035] The mixed solution was transferred to a reactor and reacted at 110°C for 18 hours;
[0036] After the reaction is completed, the product is collected by centrifugation to obtain the metal organic framework ZIF67 material;
[0037] Step 2: Prepare core-shell structure composite metal organic framework materials using epitaxial growth method:
[0038] Disperse 1.5 g of the metal organic framework ZIF67 material prepared in the first step and 4 g of 2-methylimidazole in 180 ml of methanol, and continue stirring until uniform to obtain solution C;
[0039] Dissolve 0.3 g of ferric nitrate, 0.3 g of cobalt nitrate, 0.3 g of nickel nitrate, 0.3 g of copper nitrate and 0.3 g of molybdenum nitrate in 50 ml of methanol and continue stirring until homogeneous to obtain solution D;
[0040] Solution D was slowly added to solution C, followed by continuous stirring for 8 hours at 600 rpm;
[0041] After the reaction is completed, the product is collected by centrifugation to obtain a core-shell structured composite metal-organic framework material.
[0042] The application of the core-shell structure composite metal organic framework sulfur catalyst prepared in Example 1 is as follows: the core-shell structure composite metal organic framework sulfur catalyst and pure phase nano sulfur powder are placed in a ball mill at a mass ratio of 1:3, and mixed for 5 hours using a planetary ball mill at a speed of 600 rpm. The mixture obtained after ball milling is placed in a tubular furnace under nitrogen protection, and heat treated at 150° C. for 12 hours to obtain a sulfur-composite metal organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
[0043] The scanning electron microscope image of the core-shell structure composite metal organic framework sulfur catalyst prepared in Example 1 is shown in Figure 1 The discharge capacity cycle diagram of the sulfur-composite metal organic framework material prepared in Example 1 is shown in Figure 2 .
[0044] Example 2: A method for preparing a core-shell structured composite metal organic framework sulfur catalyst, comprising the following steps:
[0045] Step 1: Prepare the metal organic framework ZIF67 material using the solvent method:
[0046] Dissolve 3 g of 2-methylimidazole in 10 ml of deionized water and continue stirring until homogeneous to obtain solution A;
[0047] Dissolve 0.1 g of cobalt acetate and 0.05 g of hexadecyltrimethylammonium bromide in 30 ml of deionized water and continue stirring until uniform to obtain solution B;
[0048] Solution B was added to solution A, followed by continuous stirring for 3 hours at 600 rpm;
[0049] The mixed solution was transferred into a reactor and reacted at 95°C for 12 hours;
[0050] After the reaction is completed, the product is collected by centrifugation to obtain the metal organic framework ZIF67 material;
[0051] Step 2: Prepare core-shell structure composite metal organic framework materials using epitaxial growth method:
[0052] Disperse 1 g of the metal organic framework ZIF67 material prepared in the first step and 3 g of 2-methylimidazole in 150 ml of methanol, and continue stirring until uniform to obtain solution C;
[0053] Dissolve 0.1 g of ferric nitrate, 0.1 g of cobalt nitrate, 0.1 g of nickel nitrate, 0.1 g of copper nitrate and 0.1 g of molybdenum nitrate in 30 ml of methanol and continue stirring until homogeneous to obtain solution D;
[0054] Solution D was slowly added to solution C, followed by continuous stirring for 6 hours at 500 rpm;
[0055] After the reaction is completed, the product is collected by centrifugation to obtain a core-shell structured composite metal-organic framework material.
[0056] The application of the core-shell structure composite metal organic framework sulfur catalyst prepared in Example 2 is as follows: the core-shell structure composite metal organic framework sulfur catalyst and pure phase nano-sulfur powder are placed in a ball mill at a mass ratio of 1:2, and mixed for 3 hours using a planetary ball mill at a speed of 500 rpm. The mixture obtained after ball milling is placed in a tubular furnace under nitrogen protection, and heat treated at 100°C for 8 hours to obtain a sulfur-composite metal organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
[0057] Example 3: A method for preparing a core-shell structured composite metal organic framework sulfur catalyst, comprising the following steps:
[0058] Step 1: Prepare the metal organic framework ZIF67 material using the solvent method:
[0059] Dissolve 5 g of 2-methylimidazole in 20 ml of deionized water and continue stirring until homogeneous to obtain solution A;
[0060] Dissolve 0.5 g of cobalt acetate and 0.2 g of hexadecyltrimethylammonium bromide in 60 ml of deionized water and continue stirring until uniform to obtain solution B;
[0061] Solution B was added to solution A, followed by continuous stirring for 6 hours at a speed of 1200 rpm;
[0062] The mixed solution was transferred to a reactor and reacted at 115°C for 24 hours;
[0063] After the reaction is completed, the product is collected by centrifugation to obtain the metal organic framework ZIF67 material;
[0064] Step 2: Prepare core-shell structure composite metal organic framework materials using epitaxial growth method:
[0065] Disperse 2 g of the metal organic framework ZIF67 material prepared in the first step and 5 g of 2-methylimidazole in 200 ml of methanol, and continue stirring until uniform to obtain solution C;
[0066] Dissolve 0.5 g of ferric nitrate, 0.5 g of cobalt nitrate, 0.5 g of nickel nitrate, 0.5 g of copper nitrate and 0.5 g of molybdenum nitrate in 60 ml of methanol and continue stirring until homogeneous to obtain solution D;
[0067] Solution D was slowly added to solution C, followed by continuous stirring for 12 h at 800 rpm;
[0068] After the reaction is completed, the product is collected by centrifugation to obtain a core-shell structured composite metal-organic framework material.
[0069] The application of the core-shell structure composite metal organic framework sulfur catalyst prepared in Example 3 is as follows: the core-shell structure composite metal organic framework sulfur catalyst and pure phase nano-sulfur powder are placed in a ball mill at a mass ratio of 1:5, and mixed for 5 hours using a planetary ball mill at a speed of 800 rpm. The mixture obtained after ball milling is placed in a tubular furnace under nitrogen protection, and heat treated at 200°C for 24 hours to obtain a sulfur-composite metal organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
Claims
1. A method for preparing a core-shell structured composite metal organic framework sulfur catalyst, characterized in that: The metal organic framework ZIF67 material is prepared by a solvent method, and then a high entropy metal organic framework coating layer is grown on the surface of the metal organic framework ZIF67 material by an epitaxial growth method. The formed core-shell structure composite metal organic framework material is a sulfur catalyst.
2. The method for preparing a core-shell structure composite metal organic framework sulfur catalyst according to claim 1, characterized in that: The specific steps include: Step 1: Prepare the metal organic framework ZIF67 material using the solvent method: Dissolve 3-5 g of 2-methylimidazole in 10-20 ml of deionized water and continue stirring until uniform to obtain solution A; Dissolve 0.1-0.5 g of cobalt acetate and 0.05-0.2 g of hexadecyltrimethylammonium bromide in 30-60 ml of deionized water, and continue stirring until uniform to obtain solution B; Solution B is added to solution A, followed by continuous stirring for 3 to 6 hours at a speed of 600 to 1200 rpm; The mixed solution was transferred to a reaction vessel and reacted at 95-115°C for 12-24 hours; After the reaction is completed, the product is collected by centrifugation to obtain the metal organic framework ZIF67 material; Step 2: Prepare core-shell structure composite metal organic framework materials using epitaxial growth method: Disperse 1-2 g of the metal organic framework ZIF67 material prepared in the first step and 3-5 g of 2-methylimidazole in 150-200 ml of methanol, and continue stirring until uniform to obtain solution C; Dissolve 0.1-0.5 g of ferric nitrate, 0.1-0.5 g of cobalt nitrate, 0.1-0.5 g of nickel nitrate, 0.1-0.5 g of copper nitrate and 0.1-0.5 g of molybdenum nitrate in 30-60 ml of methanol, and continue stirring until uniform to obtain a solution D; Slowly add solution D to solution C, and then continue stirring for 6 to 12 hours at a speed of 500 to 800 rpm; After the reaction is completed, the product is collected by centrifugation to obtain a core-shell structured composite metal-organic framework material.
3. Use of the core-shell structure composite metal organic framework sulfur catalyst according to claim 1 or 2 as a sulfur catalyst for sodium-sulfur batteries.
4. The use of the core-shell structure composite metal organic framework sulfur catalyst according to claim 3 as a sulfur catalyst for sodium-sulfur batteries, characterized in that: Sulfur is doped into a core-shell structured composite metal-organic framework material by ball milling and hot melting methods to obtain a sulfur-composite metal-organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
5. The use of the core-shell structure composite metal organic framework sulfur catalyst according to claim 4 as a sulfur catalyst for sodium-sulfur batteries, characterized in that: The specific process is: put the core-shell structure composite metal organic framework sulfur catalyst and pure phase nano sulfur powder into a ball mill at a mass ratio of 1: (2 to 5), use a planetary ball mill to mix and treat for 3 to 5 hours at a rotation speed of 500 to 800 rpm, put the mixture after ball milling into a tubular furnace under nitrogen protection, and heat treat it at 100 to 200°C for 8 to 24 hours to obtain a sulfur-composite metal organic framework material, which is used as a positive electrode material for a sodium-sulfur battery.
